Intensity of Alchohol Consumption, Peer Pressure and Popularity of Adolescent in NTT - Pidi Seme, Anunsiana Roswita; Wijaya, R. Pasifikus Ch.; Benu, Juliana Marlin Y (Journal of Health and Behavioral Science, 2023)
Adolescence is a time of transition from child to adult. At this point there are various biological and psychological changes that affect the nature of the individual in relationships. Peers are one of the most important factors and should not be underestimated in adolescence. Peer pressure can have a positive or negative impact. Peer pressure and popularity can influence individuals' behavior. The purpose of this study was to determine the association between the intensity of alcohol consumption in relation to peer pressure and popularity among adolescents in NTT. This type of research is quantitative correlation and is tested using Spearman's correlation hypothesis test. The sample in this study included 361 adolescents aged 15-20 years. The sampling technique was carried out according to the convenience sampling method. Collection of data using a questionnaire and analysis using the JASP program. The results of this study indicate that there is an association between peer pressure and the intensity of alcohol consumption (r = 0.165 p = 0.002) and an association between popularity and the intensity of alcohol consumption (r = 0.155 p = 0.155 p = 0.003), such that H0 discarded and H1 is received. The conclusion is that there is a correlation between peer pressure and popularity with the intensity of alcohol consumption.